Simulated Computational Model Lesson Improves Foundational Systems Thinking Skills and Conceptual Knowledge in iology Students. (20th June 2018) - Bergan-Roller, Heather E; Galt, Nicholas J; Chizinski, Christopher J; Helikar, Tomáš; Dauer, Joseph T
Abstract: It is important for undergraduate biology students to understand biological phenomena from a systems perspective because it is important for solving world problems related to the life sciences (e.g., medical and environmental). Unfortunately, students have few opportunities to develop the skills and conceptual knowledge required for a systems perspective. Simulated computational models are promising tools to help students achieve a systems perspective. We examined one lesson that uses simulations of a computational model to teach students about cellular respiration, and we report on its effectiveness to improve systems thinking skills and conceptual knowledge. Concept models revealed that the lesson helped the students identify, relate, and interconnect the components of cellular respiration, thereby improving aspects of their systems thinking skills and conceptual knowledge. We discuss how learning was affected by how the students interacted with the computational model.